2007
DOI: 10.1542/peds.2006-2767
|View full text |Cite
|
Sign up to set email alerts
|

Restless Legs Syndrome: Prevalence and Impact in Children and Adolescents—The Peds REST Study

Abstract: These population-based data suggest that restless legs syndrome is prevalent and troublesome in children and adolescents, occurring more commonly than epilepsy or diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
214
8
13

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 360 publications
(249 citation statements)
references
References 54 publications
14
214
8
13
Order By: Relevance
“…Three prior large epidemiological studies used an expert consensus definition of clinically significant RLS ("RLS sufferers") as symptoms occurring at least twice weekly with moderate to severe distress [12][13][14]. The CH-RLSq13 included these frequency and distress items to define RLS severity allowing comparison of results.…”
Section: Methodsmentioning
confidence: 99%
“…Three prior large epidemiological studies used an expert consensus definition of clinically significant RLS ("RLS sufferers") as symptoms occurring at least twice weekly with moderate to severe distress [12][13][14]. The CH-RLSq13 included these frequency and distress items to define RLS severity allowing comparison of results.…”
Section: Methodsmentioning
confidence: 99%
“…One study indicated that 71% of the children having RLS symptoms had at least one biological parent with RLS. 14 As in the adult population, in samples of children and adolescents, RLS symptoms were associated with sleep disturbances including sleep onset or sleep maintenance insomnia. 14 To our knowledge, there are no extant studies that have investigated the presence of RLS in biological caregivers of children with ASD or the relationships of these symptoms to caregiver HRQoL.…”
Section: Introductionmentioning
confidence: 92%
“…Two studies on the prevalence of RLS performed in children found rates of 31.7% and 5.9% respectively 124,125 . The study by Laberge and colleagues 125 in Canada, assessed the prevalence and interactions between certain sleep disorders.…”
Section: Epidemiologymentioning
confidence: 99%
“…In 2007, Picchietti and colleagues 124 conducted a study to assess the prevalence of RLS in children, using the criteria of IRLSSG. A prevalence of 1.9% of children between 8 and 11 years old, and 2.0% of children between 12 and 17 years old.…”
Section: Epidemiologymentioning
confidence: 99%